E2F6 functions as a competing endogenous RNA, and transcriptional repressor, to promote ovarian cancer stemness. Issue 3 (25th January 2019) - Cheng, Frank H. C.; Lin, Hon‐Yi; Hwang, Tzy‐Wei; Chen, Yin‐Chen; Huang, Rui‐Lan; Chang, Chia‐Bin; Yang, Weiqin; Lin, Ru‐Inn; Lin, Ching‐Wen; Chen, Gary C. W.; Mai, Shu‐Yuan; Lin, Jora M. J.; et al.
Abstract : Ovarian cancer is the most lethal cancer of the female reproductive system. In that regard, several epidemiological studies suggest that long‐term exposure to estrogen could increase ovarian cancer risk, although its precise role remains controversial. To decipher a mechanism for this, we previously generated a mathematical model of how estrogen‐mediated upregulation of the transcription factor, E2F6, upregulates the ovarian cancer stem/initiating cell marker, c‐Kit, by epigenetic silencing the tumor suppressor miR‐193a, and a competing endogenous (ceRNA) mechanism. In this study, we tested that previous mathematical model, showing that estrogen treatment of immortalized ovarian surface epithelial cells upregulated both E2F6 and c‐KIT, but downregulated miR‐193a . Luciferase assays further confirmed that microRNA‐193a targets both E2F6 and c‐Kit . Interestingly, ChIP‐PCR and bisulphite pyrosequencing showed that E2F6 also epigenetically suppresses miR‐193a, through recruitment of EZH2, and by a complex ceRNA mechanism in ovarian cancer cell lines. Importantly, cell line and animal experiments both confirmed that E2F6 promotes ovarian cancer stemness, whereas E2F6 or EZH2 depletion derepressed miR‐193a, which opposes cancer stemness, by alleviating DNA methylation and repressive chromatin. Finally, 118 ovarian cancer patients with miR‐193a promoter hypermethylation had poorer survival than those without hypermethylation. These results suggest that an estrogen‐mediated E2F6 ceRNA network epigenetically and competitively inhibits microRNA‐193a activity, promoting ovarian cancer stemness and tumorigenesis. Abstract : Estrogen‐mediated E2F6 competing endogenous network epigenetically and competitively inhibits microRNA‐193a activity, promoting ovarian cancer stemness and tumorigenesis.